Training to teach science: experimental evidence from Argentina - Albornoz, Facundo; Anauati, Victoria; Luzuriaga, Maria; Furman, Melina; Podesta, Maria Eugenia; Taylor, Ines (Oxford University Press, 2019)
We evaluate the learning impact of different teacher training methods using a random controlled trial implemented in 70 state schools in Buenos Aires, Argentina. A control group receiving standard teacher training was compared with two alternative treatment arms: providing a structured curriculum unit or receiving both the unit and weekly coaching. Following a 12-week intervention, there are substantial learning gains for students whose teachers were trained using structured curriculum units, as well as for those whose teachers received coaching (between 55% and 64% of a standard deviation more than those students in the control group). Coaching teachers does not appear to be a cost-effective, as the unit cost per 0.1 standard deviation is more than twice the cost of using only the structured curriculum unit. However, additional coaching is particularly beneficial for inexperienced teachers with less than 2 years of teaching Science. Coaching teachers also showed specific gains for girls, who both learned and declared to enjoy science lessons more. Higher-performing students especially benefited from both interventions, with students from coached teachers performing particularly well in harder questions. Using structured curriculum units and providing coaching also affected teacher perceptions: teachers expressed that they enjoyed teaching Science more, taught more hours of Science and that their students developed more skills. Results from a follow-up survey suggest persistent change in teacher practice, with the vast majority reporting using the structured curriculum unit one year after the intervention.